Modifiable risk factors that mediate the effect of insomnia on the risk of low back pain: a network mendelian randomization study - WeiSong Lu; YongQuan Wang; Yue An; MengZe Li; Sen Wang; Jie Lian; Hegui Xu (Hereditas)
Abstract Background Low back pain (LBP) and insomnia are common global health issues, but their relationship and potential mediators remain unclear. This study aimed to explore the impact of insomnia on LBP using mendelian randomization (MR) methods and analyze the mediating role of modifiable factors. Methods Univariable MR (UVMR) analysis was employed to examine the causal relationship between insomnia and LBP, as well as the association between modifiable factors [smoking, alcohol consumption, body mass index (BMI), and type 2 diabetes (T2DM)] and LBP. Subsequently, multivariable MR (MVMR) analysis was conducted to explore the impact of insomnia on the mediation of LBP risk by modifiable factors. Results In the UVMR analysis, insomnia [odds ratio (OR) = 2.95, 95%CI: 2.33–3.72)] and BMI (OR = 1.18, 95%CI: 1.02–1.37) were positively associated with the prevalence of LBP. The effects of smoking, alcohol consumption, and T2DM on LBP were not significant (P > 0.05). In the MVMR analysis, the proportion of mediation of BMI on the relationship between insomnia and LBP was 7.12%. Conclusion This study revealed the causal relationship between insomnia and LBP using MR methods for the first time, and identified the mediating role of BMI. These findings offer new insights into understanding the relationship between insomnia and LBP, informing the prevention and treatment of these two health issues.